Soil Water Retention Behaviour of a Sandy Clay Fill Material. (2016) - Toll, D.G.; Asquith, J.D.; Hughes, P.N.; Osinski, P.
Abstract: The performance of transportation networks is critically dependent on the performance of cutting and embankment slopes. An instrumented embankment has been established at Nafferton farm in North East England to investigate the response of an embankment to changing climatic conditions. Higher pore water pressures (near to hydrostatic) were observed during winter months (typically January) falling back to lower values in March. The pore water pressures showed generally positive values in the upper 3 m of the embankment although suctions existed at 4.5 m depth. Soil water retention curves (SWRC) are essential to understand the changes in water content and suction that can take place during seasonal cycles and during extreme weather events. SWRCs for the embankment soil have been measured in the laboratory using novel high suction tensiometer based equipment. The results confirm that wetting and drying paths for the soil show significant hysteresis. The major differences occur in the first cycle of drying and wetting and smaller differences are seen in subsequent scanning curve paths.